Terra sem mal: o mito Guarani na demarcação de terras indígenas - Rocha, Joana D'arc Portella (2010)
This dissertation is the establishment of a dialectical reflection involving the process of demarcation of indigenous lands and the myth Mbyá of No Misfortune Land, trying to understand if, between these two variables, there is a line, and detecting to which extent the myth is considered. The landscape is the lens through which the theme was observed; as the technique of documentary research, "indirect documentation", permitted the use of research sources such as books, magazines, newspapers, separate publications, theses, and thus providing a framework that actually aids the understanding of the universe search. We tried to get the understanding of Brazilian Indian law, as well as the historical evolution that has made it. Therefore, as they help maintain the perpetuation of the condition "tutelary" for the indigenous, from the conquest of the current Brazilian territory to this present day. On the other hand, we sought to reflect on the indigenous society within broader contexts, while owners of land in Brazil, contrary to his crystallized image, which endures to the current days, after more than five centuries. In the analysis and discussion of the data was clear that the appropriation of the myth by the Guarani Indians Mbyá is connected to the foundation of their villages, based on its relationship with nature, either symbolically or through practice, and finally, his life is imbued with relations based on mythical precepts and their traditions are put into practice for centuries. The participation of Indians in the working teams of FUNAI, involving technical processes and bureaucratic and that require specialists, has been more as a labor force unspecialized. The historical process responsible for engendering the indigenous laws, resulting from contact of Europeans with native indigenous population, to this day shows that they served only to legitimize the conquest of their land. The right to exist as people or their difference always had been denied to Indians in Brazil and since 1500. The process of cannibalistic was devouring either the material and cultural of the Indians civilization by the conquering civilization. The inability of the Indians, absolute or relative, and its consequent protection, are present in indigenous Brazilian law, the only difference is the way that the conquering State considers the indigenous. Even so-called "advances" of Constitution of 1988 did not eliminate this situation.